2008
DOI: 10.1080/13651500801993241
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole: 6-month outcomes in a retrospective naturalistic study

Abstract: Aim. The efficacy of aripiprazole has been demonstrated in randomised controlled trials, but due to inclusion and exclusion criteria, these may not be representative of clinical practice. The aim of this naturalistic study was to investigate patients from an acute mental health trust who received aripiprazole, using treatment discontinuation as a primary outcome measure. Method. All patients with schizophrenia or schizoaffective disorder who had received aripiprazole were identified from pharmacy records, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Twoyear outcome data have previously been reported for these cohorts [Deslandes et al 2009a[Deslandes et al , 2009b. This study reported an additional 3 years of follow up for patients continuing either treatment at 2 years.…”
Section: Designmentioning
confidence: 82%
See 2 more Smart Citations
“…Twoyear outcome data have previously been reported for these cohorts [Deslandes et al 2009a[Deslandes et al , 2009b. This study reported an additional 3 years of follow up for patients continuing either treatment at 2 years.…”
Section: Designmentioning
confidence: 82%
“…This was a retrospective, naturalistic follow-up study of patients with a diagnosis of schizophrenia or schizoaffetive disorder, prescribed RLAI or aripiprazole tablets in clinical practice in the 2 years following their respective UK introductions. Two-year outcome data have previously been reported for these cohorts [Deslandes et al 2009a, 2009b]. This study reported an additional 3 years of follow up for patients continuing either treatment at 2 years.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation